Blinding and sham control methods in trials of physical, psychological, and self-management interventions for pain (article II): a meta-analysis relating methods to trial results. Issue 3 (11th March 2023) - Hohenschurz-Schmidt, David; Draper-Rodi, Jerry; Vase, Lene; Scott, Whitney; McGregor, Alison; Soliman, Nadia; MacMillan, Andrew; Olivier, Axel; Cherian, Cybill Ann; Corcoran, Daniel; Abbey, Hilary; Freigang, Sascha; et al.
Abstract : Supplemental Digital Content is Available in the Text. Abstract: Sham interventions in randomized clinical trials (RCTs) of physical, psychological, and self-management (PPS) therapies for pain are highly variable in design and believed to contribute to poor internal validity. However, it has not been formally tested whether the extent to which sham controls resemble the treatment under investigation consistently affects trial outcomes, such as effect sizes, differential attrition, participant expectancy, and blinding effectiveness. Placebo- or sham-controlled RCTs of PPS interventions of clinical pain populations were searched in 12 databases. The similarity of control interventions to the experimental treatment was rated across 25 features. Meta-regression analyses assessed putative links between employed control interventions, observed effect sizes in pain-related outcomes, attrition, and blinding success. The sample included 198 unique control interventions, dominated by manual therapy and chronic musculoskeletal pain research. Meta-analyses indicated small-to-moderate benefits of active treatments over control interventions, across subgroups of manual therapies, exercise, and rehabilitation, and psychological intervention trials. Multiple meta-regression modelling demonstrated that similarity between sham control and tested interventions predicted variability in pain-related outcomes, attrition, and blinding effectiveness. Influential variables were differences relating to the extent of intervention exposure, participant experience, and treatment environments. The results support the supposed link between blinding methods and effect sizes, based on a large and systematically sourced overview of methods. However, challenges to effective blinding are complex and often difficult to discern from trial reports. Nonetheless, these insights have the potential to change trial design, conduct, and reporting and will inform guideline development.